Clinicopathological analysis of eyelid malignancies - A review of 85 cases - Satish M. Kale; Surendra B. Patil; Nishant Khare; Mahantesh Math; Arvind Jain; Sumeet Jaiswal (Indian Journal of Plastic Surgery)
Background: Resection of eyelid malignancies leads to complex reconstructive problems due to the functional and aesthetic importance of an eyelid. Hence, a large number of such cases are referred to plastic surgery facilities. Eyelid malignancies are of varied histological types and the western and Asian data have considerable variations in case distribution and presentation. This study is an attempt to characterise these tumours in the Indian population. Materials and Methods: The present study is a retrospective analysis of 85 consecutive cases of eyelid malignancies that reported to a tertiary health care facility in central India over a 15-year period starting from January 1996 up to December 2009. The cases were analysed for their age of presentation, sex distribution, tumour location, delay in seeking treatment, recurrence rate and variations with respect to the pathological subtype. Observations: Mean age of presentation for all the malignancies was 59 years. The median age of presentation was 65 years for basal call carcinoma (BCC), 58 years for sebaceous gland carcinoma (SGC), 55 years for squamous cell carcinoma (SCC) and 45 years for malignant melanoma. There was slight female preponderance as 56.28% of the patients were females. The most common location of the tumour was lower lid (58.2%) for all the malignancies. BCC was the most common malignancy (48.2%) followed by SGC (31.2%) and SCC (13.7%). Mean duration of symptoms was 9 months (range 3-21 months). The most common presenting complaint was mass with ulceration across all histological subtypes. Other associated complaints included itching, discharge from eye, pain and ptosis. The mean size of tumour at diagnosis was 2.34 ± 0.4 cm for BCC, 2.19 ± 0.6 cm for SGC and 1.99 ± 0.7 cm for SCC. The mean rate of growth of BCC was 1.39 cm/year. The corresponding values for SGC and SCC were 3.63 and 4.89 cm/year, respectively. The rate of follow-up was 89% at 3 months, 71% at 6 months, 62% at 1 year and 31% at 5 years. Recurrence rate was 1.9% for BCC and 12.7% for SGC. Surgical methods used included wedge excision and primary closure, excision and skin grafting, and tarso-conjunctival flap. Conclusions: We recommend that the surgeons treating eyelid malignancies in India should have a high index of suspicion for SGC. A wider margin of 10 mm is recommended for SGC excision as opposed to 5 mm for BCC.